Driver Interaction with Pedestrians at Intersections - Quantifying the influence of environmental factors on driver comfort boundaries - Jaber, Leila; Thalya, Prateek (My University, 2016)
Active safety systems are constantly being enhanced, featuring more and more environmental factors and advanced algorithms. The system needs to be able to evaluate many different driving situations, and take appropriate action, at a safety critical moment. In this study, focus has been on quantifying factors’ influence on driver comfort boundaries when interacting with pedestrians at intersections. Seven factors, on two levels, were included in the study; Car speed, Pedestrian speed, Pedestrian size, Crossing angle, Crossing presence, Crossing entry and Lane width. The experiment was designed with a fractional factorial layout with the seven factors combined into 32 tasks. Additional 4 tasks were created, 3 to compare the study against two studies previously conducted, and another to analyze the learning/ adaptation effect. Participants were divided into two groups; Group 1, frequent drivers and Group 2, occasional drivers. Statistical analysis based on Linear mixed-effects models was carried out with a significance level of 0.01 for both group of drivers separately, and by combining the two groups. Factors Car speed and Crossing entry have a significant influence on Time To Collision (TTC) at brake onset for all group of drivers. The factors decreased TTC when changed from low to high level. Factors Pedestrian size and Lane width also had a significant influence on TTC at brake onset for all group of drivers. The factors increased TTC when changed from low to high level. The study was conducted with a low-fidelity simulator available at SAFER. Limitations of the simulator included participants’ lack of input from auditory and sensory sources and narrow field of view. Also, the expectancy of the pedestrian might have changed the comfort boundaries as there was only one pedestrian crossing the road in every scenario. However, even though the simulator was developed with open source software, still nearly 90% of the participants stated they experienced the environment to be natural or sort of natural and more than 95% said they behaved, or sort of behaved, as normally as they would have in a real traffic situation.
Keywords: Transport; Maskinteknik; Transport; Mechanical Engineering